Memupuk Jiwa Kreatif dan Inovatif dalam Kewirausahaan untuk Generasi Gen Z yang Lebih Baik - Mochamad Raka Putra Basarah; Edy Soesanto; Nazwa Maharani (Journal of Creative Student Research, 2025)
Higher education plays a crucial role in shaping young generations who not only possess strong academic knowledge but also strong character. In an era of globalization and advancing technology, the challenges faced by students are not limited to mastering academic material but also include their ability to interact with society empathetically and be sensitive to the social issues around them. Therefore, character development in higher education environments has become an urgent necessity that cannot be overlooked. Character development aims to instill moral values, ethics, and a sense of social responsibility in students. These values include integrity, compassion, cooperation, and a sense of responsibility toward the community. Character education involves not only academic aspects but also students' participation in activities that allow them to directly engage with society, such as community service, student organizations, and other social activities.